COMPARISON OF PROPRIOCEPTION IN INJURED AND UNINJURED KNEE JOINTS AMONG MALE PROFESSIONAL FOOTBALLERS (International Journal of Physiotherapy, 2015)
Background: Football is the world's most popular sport. There are over 240 million registered players worldwide and many more recreational footballers. The knee is a complex joint with many components making it vulnerable to a variety of injuries. The study has investigated the effect of knee proprioception error on injured and uninjured male professional footballers.Methods: This was a cross sectional comparative study with hundred and six (106) male professional footballers were selected for the study as per the selection criteria. Hundred and eighteen injured and ninety four uninjured knee samples were analysed for this study. Photographic analysis method was used to evaluate proprioception error at inner, middle and outer range of knee joint. Proprioception error of knee joint was measured at inner range, middle range and outer range for injured and uninjured groups. Data analysis found that there is significant difference in proprioception error between the groups.Result: Comparative study was performed using independent t’ test for proprioception error between knee injured and uninjured groups. P